Effects of Dietary Starch and Crude Protein Levels on Milk Production and Composition of Dairy Cows Fed High Concentrate Diet - Mustafa Güçlü Sucak; Uğur Serbester; Murat Görgülü (Turkish Journal of Agriculture: Food Science and Technology)
Effects of two dietary levels of starch and crude protein on performance of dairy cow fed low roughage level (70:30 concentrate to roughage) were investigated. Twenty eight Holstein cows were randomly assigned to one of four dietary treatments in a 2 x 2 factorial arrangement. Factors were two dietary level of starch (14% and 22%) and crude protein (15% and 18%). Wheat straw was used as sole roughage source. The study was continued 6 weeks. Dry matter intake was not affected (P>0.05) by the dietary treatments in the study. Milk and protein yield (kg/d) were higher (P